Performance evaluation of grinding and lapping operations for generating aspheric surfaces on glass moulds using vertical machining centre - Vichare, Parag Shashikant (2006)
The main purpose of the study is to investigate potentials of vertical machining centre to produce aspheric glass moulds. The use of vertical CNC machining centre is promoted in the study to make the process more flexible compared to dedicated aspheric generators used in optical industry. Glass moulds were rough ground and lapped using four diamond grinding cup wheels. Metal and resin bonded wheels were used in rough grinding and lapping operation with grit size of 151Âµm and 15Âµm respectively. Theoretical and experimental investigations of the grinding parameters and material behaviour that influence partial ductile mode have been discussed. Analysis encompasses the kinematics of the grinding process, characterization of grinding wheel topography, mechanism of material removal and conformity analysis between grinding wheel and glass mould. The grit depth of cut analysis explains the influence of the geometry of the conformity between wheel and glass mould, and which leads to some parametric relations in the grinding process. Image analysis technique was effectively used to observe the grinding wheel topography and ground surface. The experimental process results were compared with the available industrial samples and zone generation method for determining process performance. It was found that resin bonded wheel gave better surface finish and form accuracy as compared to metal bonded wheel and rest of other two samples in the rough grinding operation. Partial ductile machined area was observed in the lapping operation. Lapping results of the industrial samples were quite promising and closer to experimental samples results for both surface finish and form accuracy. It is concluded that overall performance of the process is very encouraging for producing glass moulds on the vertical CNC machining centre.